“Fertilización con N-P-K en el manejo de cosa de arroz (oryza sativa L.) en el valle del bajo mayo-San Martín” - García Rios, Edbar (2004)
The present thesis' work was realizad in the sector Chupishiña of the district of Cacatachi, department of San Martin. The climatic characteristics of the thesis area are: dry tropical forest (bs-T), rainfall: 1 200 mm/year, mean temperatura of 25ª C y relativa humidity of 75 %. The studied organism is a variety of rice called "Capirona". The performance of the crop with different levels of Nitrogen, Phosphorus and Potassium were evaluated in a land parcels and comparad with an absoluta check sample. A completely randomized block design and a factorial arrangement of 4 x 2 x 3 were used for the statistical analysis. The results show that the fertilization with NPK increases the number of full grains of rice in comparison with the check sample. The mayor quantity of full grains was reached using the following fertilization level: low Nitrogen level (138), and high Phosphorus (100) and Potassium (160) levels. The rice crop performance applying an NPK dose of 184 - 80 - 120 (see treatment 14) increases with the shoots management, reaching a production of 4 777,5 Kg/ha with a B/C of 1.25 and a profit earning capacity of 24. 73%: With an NPK combination of 161 - 50 - 80 the relation Benefits/Costs. (B/C) was higher reaching a value of 1.28, a performance of 4 514,90 Kg/ha and a profit earning capacity of 27.98% (treatment 7). In treatment 20 we obtained a higher number of fertile ears with a high dose of N (207), a low dose of P (50) and medium dose of K (120). The performance of the check sample was 2 169,80 Kg/ha with a B/C of 1.04 andan profit earning capacity of 3.88 %.